2020
DOI: 10.1111/1440-1681.13281
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of cyclosporine‐induced testicular toxicity by carvedilol and/or alpha‐lipoic acid: Role of TGF‐β1, the proinflammatory cytokines, Nrf2/HO‐1 pathway and apoptosis

Abstract: Cyclosporine is an immunosuppressive agent that is used to prevent organ rejection after organ transplantation. Due to the widespread use of this type of surgery, the effect of cyclosporine on reproduction and fertility should have a specific interest. Our aim was to assess the effect of carvedilol and/or alpha-lipoic acid on cyclosporineinduced testicular toxicity in rats. Sixty male Wistar rats were divided into six equal groups: Control; cyclosporine; cyclosporine + carvedilol; cyclosporine + alpha-lipoic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…[54,55] F I G U R E 8 Graphical representation of the possible cascades or pathways involved in the hepatoprotective effect of nilotinib against cyclosporine-A-induced liver injury. ALT, alanine aminotransferase; AST, aspartate aminotransferase; Bax, Bcl2-associated X; GSH, reduced glutathione; HO-1, hemoxygenase-1; IL-2, interleukin-2; MDA, malondialdehyde; NF-κB, nuclear factor-κB; Nrf2, nuclear factor erythroid-2 like-2; ROS, reactive oxygen species; TAC, total antioxidant capacity; γ-GT, Y-glutamyl transferase To elucidate the possible ameliorative effect of nilotinib treatment in CsA-injected rats, Nrf2 and OH-1 were addressed in the present study as CsA-treated group presented a significant reduction in nrf2 protein level and a marked decrease in mRNA expression and immunoreactivity against HO-1 in the hepatic tissue of rats and this was consistent with the previous studies which showed that CsA markedly decreased the nuclear expression of Nrf2 in rat kidneys [56][57][58] decreased Nrf2/HO-1 content in rat testicular tissue, [59] and decreased the ratio of nuclear/ total Nrf2 and HO-1 expression in rat kidney. [57,58] In the present study, nilotinib administration seems to increase Nrf2 levels in comparison to CsA-treated rats and it is considered as an Nrf2 activator.…”
Section: Effects Of Nilotinib On Histopathological Examinationsupporting
confidence: 89%
“…[54,55] F I G U R E 8 Graphical representation of the possible cascades or pathways involved in the hepatoprotective effect of nilotinib against cyclosporine-A-induced liver injury. ALT, alanine aminotransferase; AST, aspartate aminotransferase; Bax, Bcl2-associated X; GSH, reduced glutathione; HO-1, hemoxygenase-1; IL-2, interleukin-2; MDA, malondialdehyde; NF-κB, nuclear factor-κB; Nrf2, nuclear factor erythroid-2 like-2; ROS, reactive oxygen species; TAC, total antioxidant capacity; γ-GT, Y-glutamyl transferase To elucidate the possible ameliorative effect of nilotinib treatment in CsA-injected rats, Nrf2 and OH-1 were addressed in the present study as CsA-treated group presented a significant reduction in nrf2 protein level and a marked decrease in mRNA expression and immunoreactivity against HO-1 in the hepatic tissue of rats and this was consistent with the previous studies which showed that CsA markedly decreased the nuclear expression of Nrf2 in rat kidneys [56][57][58] decreased Nrf2/HO-1 content in rat testicular tissue, [59] and decreased the ratio of nuclear/ total Nrf2 and HO-1 expression in rat kidney. [57,58] In the present study, nilotinib administration seems to increase Nrf2 levels in comparison to CsA-treated rats and it is considered as an Nrf2 activator.…”
Section: Effects Of Nilotinib On Histopathological Examinationsupporting
confidence: 89%
“…In addition to its antioxidant efficacy, ALA has been widely studied for its anti-inflammatory and anti-apoptotic impacts in various disease models [13,[52][53][54]. In this context, ALA demonstrated protective efficacy against CsA-induced renal [55], pancreatic [56], testicular [57], and neurological toxicity [58]. Similarly, ALA in the present study protected against CsA-induced liver injury through modulation of oxidative stress, inflammation, and apoptosis.…”
Section: Discussionsupporting
confidence: 67%
“…Combined therapy with clopidogrel and irbesartan was found to inhibit nephritis by abolishing macrophage infiltration and thus to reduce early kidney damage caused by nephrectomy [136]. There are also some contradictory observations regarding the irbesartan ability to influence the concentration of CRP, TGF-β, TNF-alfa, IL-6, and the expression of NF-κB, ICAM-1, VCAM-1, and MCP-1 [137][138][139][140][141].…”
Section: Candesartan Irbesartanmentioning
confidence: 99%